Using the Seminar Format to Explore Pre-service Teachers’ Argumentative Abilities in English as a Foreign Language - Orellana, Pelusa (GIST – Education and Learning Research Journal, 2015)
The current study describes the introduction of seminar discussions in a literature course to track students’ growth in argument production across the semester. Sixteen students enrolled in a required teacher education course were asked to plan and facilitate a 50-minute seminar discussion on a literary text, following the Paideia Seminar protocol. The course was taught in English, although the students’ first language was Spanish. Over the course of the semester, I monitored students’ progress in developing evidence-based coherent arguments and counterarguments. Pre-service teachers not only gained expertise as seminar facilitators, but their oral and written responses to seminar issues revealed an increase in more elaborated arguments, use of textual references, counterargument production, and overall sophisticated thinking.